Motivations and benefits of quality management systems in social services: mediation of the implementation process. (19th May 2021) - Marimon, Frederic; Melão, Nuno; Bastida, Ramon
Abstract : Recent times have seen many social service organisations (SSOs) implementing quality management systems based on certifiable standards. However, little is known about the benefits of such systems, as well as to what factors influence them. To investigate this issue, the aim of this study is threefold: to analyse the composition of the benefits that SSOs may achieve with the implementation of the European Quality in Social Services (EQUASS) standard; to analyse the impact of both internal and external motivations on the benefits of the EQUASS standard; and to analyse the mediation of the implementation process of the standard between the motivations and the benefits. A questionnaire-based survey was used to collect data from 196 European SSOs. Data were analysed via factor analysis and structural equation modelling. Results show that the benefits are multidimensional, consisting of society, customer, operational, employee, and economic domains. Other findings reveal that internal and external motivations positively affect overall benefits, internal motivations positively affect the implementation process, and the implementation process positively influences overall benefits. The key insight is that internal motivations have a direct positive influence on overall benefits and an indirect positive influence through the mediation of the implementation process. Managerial and research implications of these findings are discussed.